Cardiovascular-Kidney-Metabolic Syndrome Among Healthcare Workers in Chinese Tertiary Hospital - Zhang Q; Zheng J; Wang G; Jiang S; Gao P; Sun S; Ding X; Wu Y (Dove Medical Press, 2024)
Qingqing Zhang,1,2,* Jing Zheng,1,* Guoyu Wang,1,3 Suyun Jiang,1 Peng Gao,1 Si Sun,1 Xiangwei Ding,3 Yucheng Wu3 1Department of Pan-Vascular Management Center, The Affiliated Taizhou People's Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, Jiangsu, People's Republic of China; 2Department of Endocrinology, The Affiliated Taizhou People's Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, Jiangsu, People's Republic of China; 3Department of Cardiology, The Affiliated Taizhou People's Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Yucheng Wu; Xiangwei Ding, Email 2567181759@qq.com; dingxw1208@126.comObjective: To determine the prevalence of Cardiovascular-Kidney-Metabolic (CKM) Syndrome and identify risk factors, including occupational factors, lifestyle factors and clinical measurements, and female-specific risk enhancers among healthcare workers in China.Methods: A cross-sectional study was conducted among healthcare workers at Taizhou People's Hospital between April and May 2024. We collected data through surveys and laboratory results. Univariate and multivariate logistic regression analyses were performed to identify predictors of CKM syndrome and female-specific risk enhancers.Results: A total of 1110 participants were recruited (197 male; 913 female; mean age 34.8± 7.9). Almost 90% of male healthcare workers and 60% of female healthcare workers met the criteria for CKM syndrome (stage 1 or higher). Additionally, most male CKM syndrome patients were in stages 2- 3 (53.81%), while most female CKM syndrome patients were in stage 1 (35.82%). Multivariate logistic regression analysis revealed that, compared to those with over 20 years of work duration, a work duration of less than 10 years was a protective factor for CKM Syndrome. Additionally, more than 8 hours of sedentary time was identified as a risk factor compared to less than 2 hours (OR = 1.376, 95% CI 1.027- 1.844, P < 0.05). Receiver operating characteristic analysis showed that body mass index (BMI) was superior to fasting plasma glucose, glycated hemoglobin, triglycerides, and the triglyceride glucose product index in predicting CKM Syndrome, with area under the curve values of 0.884 vs 0.638, 0.708, 0.745, and 0.761, respectively (P < 0.05 for all). BMI was identified as an independent risk factor for female-specific risk enhancers.Conclusion: CKM syndrome is prevalent among healthcare workers in Chinese tertiary hospitals, with males generally presenting at more advanced stages than females. BMI is a key predictor of CKM syndrome and female-specific risk enhancers.Keywords: cardiovascular-kidney-metabolic syndrome, BMI, healthcare workers, triglyceride glucose product index